2014
DOI: 10.2169/internalmedicine.53.1384
|View full text |Cite
|
Sign up to set email alerts
|

Histiocytic Sarcoma of the Bile Duct

Abstract: An 80-year-old man was admitted with anorexia, a high fever and general icterus. Laboratory examinations revealed remarkable inflammation and elevation of liver/biliary enzymes. Computed tomography (CT) showed a high-density lesion in the bile duct, and endoscopic retrograde cholangiopancreatography (ERCP) disclosed an oval filling defect mimicking choledocholithiasis. Plastic stents were inserted to treat the acute cholangitis; however, the patient's symptoms recurred. An erythematous hypervascular mass obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Less often, primary lung disease resembling pulmonary LCH [196], and primary parotid gland involvement have been described [6]. The disease may spread to other organs, i. e. lungs, liver, spleen [20], bile ducts [141], and CNS; in the latter, both intracerebral lesions [46,80,164] and lesions in the spinal cord have been described [161]. Also, leukemia-like spread of cells in the blood may occur [36].…”
Section: Histiocytic Sarcoma (Histiocytic Mh)mentioning
confidence: 99%
“…Less often, primary lung disease resembling pulmonary LCH [196], and primary parotid gland involvement have been described [6]. The disease may spread to other organs, i. e. lungs, liver, spleen [20], bile ducts [141], and CNS; in the latter, both intracerebral lesions [46,80,164] and lesions in the spinal cord have been described [161]. Also, leukemia-like spread of cells in the blood may occur [36].…”
Section: Histiocytic Sarcoma (Histiocytic Mh)mentioning
confidence: 99%
“…Presentation of abdominal pain, dysphagia, weight lost, nausea, vomiting, diarrhea, small bowel obstruction, and GI bleeding have all been reported. Involvement of the gallbladder and bile duct – as in our case – are extremely rare and have just recently been reported [18]. The appearance of circulating histiocytes in the peripheral blood of our patient as part of disease progression (“leukemic phase”) is extremely rare.…”
Section: Discussionmentioning
confidence: 55%
“…14 of those cases involved the luminal gastrointestinal tract including the stomach, small intestine, large intestine, and anus. The one additional case involved a common bile duct mass mimicking choledococholelitiasis . Since this review article, one additional case study has reported histiocytic sarcoma of the espophagus and 2 additional cases were reported in the stomach .…”
Section: Discussionmentioning
confidence: 92%